1999
DOI: 10.1097/00003072-199908000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tc-99m EC and Tc-99m DTPA Captopril Scintigraphy To Diagnose Renal Artery Stenosis

Abstract: There is no significant difference between Tc-99m EC and Tc-99m DTPA captopril scintigraphy for detecting renal artery stenosis. However, because of the better imaging characteristics and more confident interpretation provided by the dramatic changes in the degree of renogram abnormality after captopril intervention, Tc-99m EC captopril scintigraphy should be used, particularly in patients with decreased renal function or branch artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In a MEDLINE search (October 06, 2005) using key words (DTPA AND EC AND Scintigraphy AND Renal) only one paper comparing the two methods was retrieved (10). This paper compares the diagnostic accuracy of 99m Tc-EC with 99m Tc-DTPA in the assessment of renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a MEDLINE search (October 06, 2005) using key words (DTPA AND EC AND Scintigraphy AND Renal) only one paper comparing the two methods was retrieved (10). This paper compares the diagnostic accuracy of 99m Tc-EC with 99m Tc-DTPA in the assessment of renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…With the same purpose our group previously compared the performance of 99 mTc-EC with 99 mTc-DTPA for the diagnosis of renal artery stenosis. 13 • 14 We found that there is no statistically significant difference between 99 mTc-EC and 99m Tc-DTPA captopril scintigraphies for detecting renal artery stenosis. Nevertheless, due to its better imaging characteristics and more confident interpretation provided by the dramatic changes in the renogram grade after captopril intervention, 99m Tc-EC captopril scintigraphy can be used particularly in patients with decreased renal function or branch artery stenosis.…”
Section: Discussionmentioning
confidence: 74%
“…There is a great range of sensitivity reported-from 49% to 93% [18][19][20][21][22][23][24]. The European Captopril Radionuclide Test Multicenter Study Group studied 424 patients and found a sensitivity of 73.2% and a specificity of 90.7% for the test, provided that DSA showed a stenosis >70% [8].…”
Section: Discussionmentioning
confidence: 99%
“…A further, larger meta-analysis involving 63 studies in adult patients comparing different modalities of investigations to diagnose RVD gave a sensitivity of 81% for captoprilenhanced scintigraphy. The isotope studies have shown a lower specificity in patients with abnormal renal function [16,20]. Some studies have addressed whether the success of a later intervention can be predicted by captopril renal scintigraphy in children.…”
Section: Discussionmentioning
confidence: 99%